Wealth and history: An update - Daniel Waldenström (Research Institute of Industrial Economics (IFN), 2021)
This paper analyzes new evidence on long-run trends in aggregate wealth accumulation and wealth inequality in Western countries. The new findings suggest that wealth-income ratios were lower before World War I than previously claimed, that wealth concentration fell over the past century and has remained low in Europe but increased in the United States, that wealth has changed from being dominated by elite-owned fortunes to consist mainly of popular wealth, and that capital shares in national income have been relatively stable over time, especially in the postwar era. These findings cast doubt on claims that a low-tax, low-regulation capitalism will generate extreme capital accumulation, and that persistent wealth equalization requires large shocks to capital coming from wars or progressive taxation. Instead, institutions that promote household wealth accumulation from below appear to be key for understanding the long-run evolution of wealth in Western societies.
Keywords: D30; E21; N30; 330; Wealth-income ratios; Wealth Inequality; Capital share; Economic history